Red blood cell indices in different hemoglobinopathies: A cross-sectional study in Eastern India - Ayandip Nandi; Manas Talukdar; Saikat Bhattacharya; Susruta Sen; Supratik Biswas; Kuntal Roy (Indian Journal of Pathology and Microbiology)
Introduction: Beta thalassemia and hemoglobin (HbE)-related hemoglobinopathies are common public health problems in developing countries. High-performance liquid chromatography (HPLC) is currently the diagnostic test of choice for carrier detection, but it is costly. Hence, some initial screening and complementary tests are required, which can be affordable. Aims: To find out the distribution of different red blood cell (RBC) indices in beta thalassemia trait (BTT) and HbE-related hemoglobinopathies and to determine their significance as screening tests to distinguish between these hemoglobinopathies. Study Settings and Design: This observational cross-sectional study has been carried out at an NABL (National Accreditation Board for Testing and Calibration Laboratories)-accredited Laboratory of Eastern India with approval from the concerned Institutional Ethics Committee from January 2021 to March 2021. Methods and Material: HPLC tests and complete hemograms were performed on 2247 ethylenediaminetetraacetic acid anti-coagulated blood samples over 3 months. Patients <1 year of age or having a history of blood transfusion within the past 06 months were excluded. Statistical Analysis: One-way analysis of variance along with Bonferroni post-hoc test was performed to find out significant differences of means of mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), hemoglobin%, red blood cell (RBC) count, and red cell distribution width (RDW-CV) among concerned hemoglobinopathies. Results: The results show a significant difference of total RBC count, RDW, MCV, MCH, and MCHC between BTT and E-trait. No significant difference of mean was found between HbE homozygous and E-beta. E-trait differs from both HbE homozygous and E-beta significantly in three parameters, namely, RDW, MCV and MCH. A value of MCV at ≤73.8 fl and MCH at ≤21.9 pg may be a clue of diagnosis for BTT rather than E-trait with >90% sensitivity and >80% specificity. Conclusion: RBC indices vary significantly between BTT and other HbE-related hemoglobinopathies. They can specially be utilized to differentiate BTT and E-trait as supportive tests in addition to the gold standard test of HPLC.